2013
DOI: 10.1371/journal.pone.0070172
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Individual and Inter-Strain Variations in Zebrafish Locomotor Ontogeny

Abstract: Zebrafish exhibit remarkable alterations in behaviour and morphology as they develop from early larval stages to mature adults. In this study we compare the locomotion parameters of six common zebrafish strains from two different laboratories to determine the stability and repeatability of these behaviours. Our results demonstrate large variability in locomotion and fast swim events between strains and between laboratories across time. These data highlight the necessity for careful, strain-specific controls wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 43 publications
7
47
0
Order By: Relevance
“…Some studies demonstrated that a large variability exists in the individual motion and shoaling tendency of the zebrafish according to their age or strain. For example, adults AB and casper zebrafish swim longer distance than ABstrg, EK, TU or WIK zebrafish [51]. Likewise, the interindividual distance between shoal members decreases from 16 body length to 3.5 body length between day 7 and five months after fertilization [52].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that a large variability exists in the individual motion and shoaling tendency of the zebrafish according to their age or strain. For example, adults AB and casper zebrafish swim longer distance than ABstrg, EK, TU or WIK zebrafish [51]. Likewise, the interindividual distance between shoal members decreases from 16 body length to 3.5 body length between day 7 and five months after fertilization [52].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, assessment of movement can be done in embryos and it was recently suggested as a potential assay for developmental neurotoxicity testing (Selderslaghs et al, 2010(Selderslaghs et al, , 2013. However, in many cases the patterns of responses as well as sensitivity to certain toxicants significantly differ between embryos and later stages (Airhart et al, 2007;Jin et al, 2009;Lange et al, 2012;Sloman and McNeil, 2012), and one particular disadvantage of embryonic stages is that spontaneous swimming activity is not yet established.…”
Section: Kes ''Locomotion Impairment'' and ''Reduction In Food Intake''mentioning
confidence: 99%
“…These published estimates of U crit cover a range of values, from c . 5 to 28 L S s −1 , which might reflect differences in methodology or test temperature (Sfakianakis et al , ), genetic variation among test populations, many of which are sourced from local pet shops and have unpublished histories (Lange et al , ), age (Gilbert et al , ) or, as suggested by this study, sex. Few studies of U crit in D .…”
Section: Discussionmentioning
confidence: 78%